2020
DOI: 10.14295/bds.2020.v23i2.1864
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of soft tissue calcifications in cone beam computed tomography images in the region of head and neck

Abstract: Objective: to evaluate the prevalence of calcifications in the soft tissues of the cervical-facial region using cone beam computed tomography (CBCT) images. Material and Methods: two hundred and ten CBCT exames was analyzed by 01 examiner previously trained, with fild of view (FOV) of 16 x 13 cm and voxel of 0.25 mm, in ICAT Vision software (Imaging Science International, Hatfield, PA, USA) in coronal, axial and sagittal sections. The following calcifications were evaluated: tonsiloliths, sialolites, calcifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Regarding CAC, we detected 4 cases with (0.69%) prevalence within the whole sample.And this is considered less than Diniz et al, study which showed prevalence (4, 76%) within the whole sample. 1 Only one case in our study was detected with ethmoidal sinolith. The presence of sinolith in the ethmoidal sinus is very rare and only 5 cases in the English literature were documented with ethmoidal sinolith as mentioned by Sava and Rusu.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Regarding CAC, we detected 4 cases with (0.69%) prevalence within the whole sample.And this is considered less than Diniz et al, study which showed prevalence (4, 76%) within the whole sample. 1 Only one case in our study was detected with ethmoidal sinolith. The presence of sinolith in the ethmoidal sinus is very rare and only 5 cases in the English literature were documented with ethmoidal sinolith as mentioned by Sava and Rusu.…”
Section: Discussionmentioning
confidence: 55%
“…04%) then tonsilloliths with (19.52%). 1 In Diniz et al, study sialoliths showed prevalence (0,47%) within the whole sample. 1 which is much less comparing to our study calcified stylohoid ligament is considered elongated if exceeded 30mm.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations